A method for determining D region ionosphere reflection height from lightning skywaves. (15th September 2021) - Zhou, Xiao; Wang, Jiaquan; Ma, Qiming; Huang, Qijun; Xiao, Fang
Abstract: The sky waves generated by lightning are used to study the ionosphere. Previous studies calculated the reflection height of the ionosphere D region based on the time delay between the ground wave and the first skywave. This paper presents a new method for detecting the ionosphere. A set of ground wave delay values are used to calculate the height corresponding to the first and second skywaves. The height is determined by comparing the minimum difference between the corresponding heights of the first and the second skywaves. The height uncertainty is better than 1.5 km. Different from the previous studies for selecting lightning within a few hundred kilometers, the new method can select lightning within 2000 km for calculation. The results show that the errors caused by the ground wave delay can be corrected. For a region where lightning occurred in 24 h, the maximum height observed at night was 88 km, while the minimum height during the day was 66.7 km. In the absence of solar flare X-rays, the height during the day is strongly correlated with the solar zenith angle. Highlights: The first and second skywaves are used to calculate the D region ionosphere reflection height. The height is determined by comparing the minimum difference between the heights of the 1st and the 2nd skywaves. The lightning within 2000 km can be selected for calculation. The height uncertainty is better than 1.5 km.